WIRELESS SMART HOME SYSTEM MENGGUNAKAN RASPBERRY PI BERBASIS ANDROID - Farisqi Panduardi; Endi Sailul Haq (Jurnal Teknologi Informasi dan Terapan, 2019)
The Technological developments from time to time proved to have given a lot of changes in people's lives. Changes for the better, like make it easier to do a job. One of the technologies developed at this time is with the development of cellular technology is not only used as a telephone and send SMS, but also can be used as a device for controlling a device. Raspberry Pi, often also called by the name Raspi, is a single board computer (Single Board Circuit / SBC), which has the size of a credit card that can perform digital data processing in accordance with orders given programming language. Then the Raspberry Pi is currently widely applied in daily life, one of which is used in smart home wifi automatic use of media-based Raspberry Pi. smart home system is a tool that can work automatically based on the input to the Android and the program that is embedded in a Raspberry Pi. wifi as a communication medium to transmit data or input from the android application that acts as a device to control home appliances remotely. In general, control of home appliances is still work manually making it less effective, objective of the smart home system design tool to create a tool that can help people to carry out activities in the house that is to control home appliances using smartphones automatically through android application.